The Extracellular Superoxide Dismutase Sod5 From Fusarium oxysporum Is Localized in Response to External Stimuli and Contributes to Fungal Pathogenicity - Wang, Qiang; Pokhrel, Ambika; Coleman, Jeffrey J. (Frontiers in Plant Science, 2021)
Reactive oxygen species (ROS) produced by hosts serve as a general defense mechanism against various pathogens. At the interaction site between the host and pathogen, host cells rapidly accumulate high concentrations of ROS, called the oxidative burst, that damage and kill the invading microbes. However, successful pathogens usually survive in a high ROS environment and have evolved strategies to overcome these detrimental effects. Here we characterized the biological function of the extracellular superoxide dismutase (SOD) FoSod5 from Fusarium oxysporum f. sp. vasinfectum. FoSOD5 is strongly up-regulated during infection of cotton, and a ΔFoSOD5 mutant was significantly reduced in virulence on cotton. Purified 6×His-FoSod5 could significantly inhibit the reduction of NBT and WST-1, indicating that FoSod5 was a functional SOD protein. Based on CRISPR/Cas9 technology, several different FoSod5 variants were generated and used to assess the secretion, expression, and subcellular localization of FoSod5 in F. oxysporum. The subcellular localization of FoSod5 is altered under different environmental conditions. During normal growth conditions, FoSod5 was primarily localized to the phialides; however in a nutrient-limited environment, FoSod5 was localized to a wide array of fungal structures including the septum and cell wall. FoSod5 is an alkaline-induced GPI protein and the GPI anchor was required for proper protein subcellular localization. The multiple mechanisms fungi utilize to tolerate the oxidative burst is indicative of the importance of this plant defense response; however the presence of a conserved extracellular SOD in many phytopathogenic fungi suggests tolerance to ROS is initiated prior to the ROS entering the fungal cell.